2017
DOI: 10.4028/www.scientific.net/msf.888.314
|View full text |Cite
|
Sign up to set email alerts
|

EDS Analysis for Fruit <i>Prunus</i> Elemental Composition Determination

Abstract: The questions of the practical usage of the analytical scanning electron microscope JSM 600 LA by JEOL company (Japan) with EDS system – microanalysis were envisaged. This device was used to study the structure and elemental composition of the fruit ash received from 6 breeds of 3 plum species. Plum fruit are rich in mineral substances, the following order of substances accumulation is characteristic for them: K > P > Ca > Mg > Na ≈ S > Fe > Zn ≈ Cu > Mn ≈ Co > N i≈ Pb. In fruit pulp K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It controls osmotic pressure, transmembrane potential, charge equilibrium, cathode-anion balance, pH-everything that makes up the homeostasis of cells and tissues [37]. In the human body, P is a part of DNA and RNA, phospholipids, phosphate esters, nucleoside phosphates-ATP, ADP, NATP, where it performs a structural and metabolic function [38].…”
Section: Tablementioning
confidence: 99%
“…It controls osmotic pressure, transmembrane potential, charge equilibrium, cathode-anion balance, pH-everything that makes up the homeostasis of cells and tissues [37]. In the human body, P is a part of DNA and RNA, phospholipids, phosphate esters, nucleoside phosphates-ATP, ADP, NATP, where it performs a structural and metabolic function [38].…”
Section: Tablementioning
confidence: 99%
“…Most recent technologies that have been developed through physiological and medical research have confirmed the important role of micronutrients in metabolic reactions and submolecular processes. However, these activities depend on the presence of certain macroand micronutrient elements in the daily human diet (Avtsyn et al, 1991;Motyleva et al, 2017;Peter and Gandhi, 2017).…”
Section: Plantsmentioning
confidence: 99%
“…Deficiency of Fe, Mn, Zn, and Cu can lead to iron deficiency anemia, impaired development of bone tissues (Mn, Cu), decreased immunity and weakening of the antioxidant defense of the body (Zn), impaired brain function (Zn, Mn), and hematopoiesis (Cu). Medical studies confirmed the important role of trace elements in metabolic reactions and sub-molecular processes, the activity of which depends on the presence of certain micronutrients in the daily human diet (Avtsyn et al, 1991;Kavita and Puneet, 2017;Motyleva et al, 2017).…”
Section: Introductionmentioning
confidence: 95%